Prohibition without protection: Marriageable age law reforms and adolescent fertility in Mexico - Audrey Au Yong Lyn (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2019)
Between 2014 and 2017, Mexican states implemented minimum marriageable age laws that banned marriages for girls below 18. In this study, I exploit the temporal and geographical variation in law implementation to estimate the impact of these civil law reforms on child marriage rates, teenage birth rates and school attendance using a difference-in-difference methodology. The results show that states adopting minimum marriageable age laws exhibited a 37% decrease in child marriage rates and a 0.9% increase in the likelihood of girls' school attendance compared to non-adopting states. However, contrary to what is expected, I find an increase in teenage birth rates by approximately 11%. To explain these findings, I present a novel theory hypothesizing that adolescent girls used pregnancy as an alternative commitment device in place of marriage. Additional results suggest that this behavioral response is likely to be stronger among girls from lower socio-economic classes due to low-income earning potential and the subsequent need for a man's financial support. An analysis of a crosssectional, nation ally representative survey on child labor further indicate that girls could have been compelled to enter consensual unions during or post-pregnancy as marriage was no Ionger allowed, exposing them to a higher risk of domestic violence, single-motherhood and abject poverty. The results highlight the importance of considering local socio-cultural contexts before applying international policy guidelines in order to eschew unintended consequences.
Keywords: J1I2; J13; J18; K15; 330; Adolescent fertility; child marriage; minimum marriageable age laws; consensualunions